Program earth : environmental sensing technology and the making of a computational planet - Gabrys, Jennifer (Electronic mediations, 2016)
"Grappling with the consequences of wiring our world, Program Earth examines how sensor technologies are programming our environments. Jennifer Gabrys suggests that the sensor-based monitoring of Earth offers the prospect of making new environments not simply as an extension of the human but rather as new "technogeographies" that connect technology, nature, and people."